Ponderations on the length of petitions and the guarantee of a speedy procedure (Revista do Tribunal Regional Federal da 3ª Região, 2020)
This article is an invitation to reflect on the need to improve the elaboration of written procedural acts as one of the means to guarantee the speed of the procedural process.
Keywords: petition; prolixity; speed; process; responsibility; reflection